Improving Students’ Mathematical Thinking And Disposition Through Probing And Pushing Questions - Titin Suryati Sukmadewi (Jurnal Matematika Integratif, 2014)
Teaching and learning math is not just an activity to develop thinking skills of students as mathematicalunderstanding, mathematical reasoning, problem solving, and mathematical communication. Moreover, teaching learning math should provide enough space for students to appreciate the usefulness of mathematics in life, showed by curiosity, concern and interest in learning mathematics, and perseveranceand confidence in problem solving. Questioning is a method that is always used by almost all mathematics teachers. What kinds of questions do our students ask? How can we make our classrooms as a place where questioning is central to learning? Let consider research related to teaching and learning mathematics with a particular focus on questions designed to provoke student thinking. The emphasis will be on how to design and use questions and questioning techniques that push students to the make connections and come to understand mathematics in a deeper way or that probe their thinking to better understand how they perceive the mathematics. Probing and pushing questions can be used as an alternative for the development of students’ mathematical thinking skills as well as students' mathematical dispositions/character building in mathematics. Keywords: mathematical thinking, mathematical disposition, probing and pushing questions, funnelingand focusing